METODE ROTATIONAL THROW MENINGKATKAN HASIL BELAJAR LEMPAR CAKRAM SISWA MTS - Muhlas, Wildan; Mujriah, Mujriah; Susilawati, Indri (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
ABSTRACT Discus throw learning in schools still faces various challenges, including limited facilities, low student participation, and the use of less varied teaching methods, resulting in suboptimal learning outcomes. This study aimed to improve discus throw learning outcomes through the implementation of the rotational throw method for eighth-grade students at MTs Al-Islahussibyan Dopang in the 2023/2024 academic year. The study employed a classroom action research method conducted in two cycles, consisting of planning, action implementation, observation, and reflection stages. The research subjects consisted of 30 eighth-grade students. Data were collected through learning outcome tests covering psychomotor, cognitive, and affective aspects, student activity observation sheets, and documentation. The data were analyzed using descriptive quantitative techniques based on the average scores and the percentage of students’ learning mastery in each cycle. The results showed that the implementation of the rotational throw method gradually improved students’ discus throw learning outcomes. Students became more active, more confident, and better able to understand the coordination of discus throw movements through systematic and repetitive practice. Students’ learning mastery increased significantly and exceeded the predetermined success indicators. These findings indicate that the rotational throw method can serve as an effective and adaptive alternative for athletics instruction, particularly in schools with limited learning facilities. ABSTRAK Pembelajaran lempar cakram di sekolah masih menghadapi berbagai kendala, seperti keterbatasan sarana, rendahnya partisipasi siswa, dan penggunaan metode pembelajaran yang kurang bervariasi sehingga hasil belajar siswa belum optimal. Penelitian ini bertujuan meningkatkan hasil belajar lempar cakram melalui penerapan metode rotational throw pada siswa kelas VIII MTs Al-Islahussibyan Dopang Tahun Pelajaran 2023/2024. Penelitian menggunakan metode penelitian tindakan kelas (classroom action research) yang dilaksanakan dalam dua siklus, meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian terdiri atas 30 siswa kelas VIII. Pengumpulan data dilakukan melalui tes hasil belajar pada aspek psikomotor, kognitif, dan afektif, lembar observasi aktivitas siswa, serta dokumentasi. Data dianalisis secara deskriptif kuantitatif berdasarkan rata-rata nilai dan persentase ketuntasan belajar siswa pada setiap siklus. Hasil penelitian menunjukkan bahwa penerapan metode rotational throw mampu meningkatkan hasil belajar lempar cakram secara bertahap. Siswa menjadi lebih aktif, lebih percaya diri, dan lebih mudah memahami koordinasi gerakan lempar cakram melalui latihan yang dilakukan secara sistematis dan berulang. Ketuntasan belajar siswa meningkat secara signifikan hingga melampaui indikator keberhasilan yang telah ditetapkan. Temuan ini menunjukkan bahwa metode rotational throw dapat menjadi alternatif pembelajaran atletik yang efektif, adaptif, dan sesuai diterapkan pada sekolah dengan keterbatasan fasilitas pembelajaran.